Posted by B8 on Friday, September 27, 2013 at 10:09pm.
The question is
(2x+1)^2-2(2x^2-1) in simplest form
Is this correct?
Did I do this correctly?
Thank you for your help.
math - Reiny, Friday, September 27, 2013 at 10:48pm
the way you typed it , I saw a subraction
(2x+1)^2 - 2(2x^2-1)
= 4x^2 + 4x + 1 - 4x^2 + 2
= 4x + 3
math - B8, Saturday, September 28, 2013 at 10:59am
Ok, I see my mistake. Thanks for explaining what I did incorrectly.
Answer This Question
More Related Questions
- Algebra - There are two solutions to | 16x - 5 | = 3. The greatest solution is ...
- algebra - Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask ...
- Math - 5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10...
- Math - I sent this in a little while back but the file got corrupted and I have ...
- algebra - x^2 +16x+64 x^2+16x=64 (x=3)^2=16x-64 16x=-64 x=-4 Check this problem ...
- math - please help - Find the HCF and LCM of: 1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - ...
- math need asap - 5/8 x+1/16 x=11/16+x 16*(5/8 x+1/16 x) = 16(11/16+x) 80 + x + ...
- Pre-Calculus - Help please If f(x)=8x and g(x)=2x+1 find (fog)(x) 16x^2+8x 16x+1...
- Math - Which of the following expressions is equivalent to (-2x^5 y^2)^4 A. -16x...
- math - Find the HCF and LCM of: 1 + 4x + 4x^2 - 16x^4.. ,1 + 2x - 8x^3 - 16x^4...